Multiple criteria analysis of environmental sustainability and quality of life in post-Soviet states. (June 2018) - Kaklauskas, A.; Herrera-Viedma, E.; Echenique, V.; Zavadskas, E.K.; Ubarte, I.; Mostert, A.; Podvezko, V.; Binkyte, A.; Podviezko, A.
Highlights: Changes in the environment and quality of life (EQIL) in republics of the former USSR was analyzed. INVAR supplements the EQIL indicators for sustainable countries with new functions. INVAR provides digital tips for improving a country's EQIL. INVAR finds EQIL indicator values allowing a country to upgrade to a desired rating. Countries with better human development, well-being and values-based values scored best in EQIL. Abstract: This article deliberates the achievements and trends relevant to environmental sustainability—Ecological Footprint (EF) and the Environmental Performance Index (EPI)—and Quality of Life Index (QLI) in 15 republics of the former USSR over the past 25 years, which have been in constant flux globally. This comparative research additionally includes nine nearby European and four Asian countries. Studies have shown that the environmental sustainability and quality of life of these countries depend on various macroeconomic, values-based, human development and well-being factors. The aggregations of analyzed data from the framework of variables were from World Bank, Country Economy and other databases, which this article details. The method applied is the Degree of Project Utility and Investment Value Assessments (INVAR). The INVAR method provided new opportunities for performing the multicriteria analysis on environmental sustainability and the quality of life. Over the course of the research, there were strong correlations established between the EPI, EF and QLI indicators on one side and the macroeconomic, values-based, human development and well-being factors from the other side.